PENERAPAN HYGIENE DAN SANITASI DI PONDOK PESANTREN AS’AD SEBERANG KOTA JAMBI TAHUN 2016 - Supriadi Supriadi; Emilia Chandra (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Various diseases based environment that is often a problem in General "as scabies, diarrhea, RESPIRATORY, caused by a less healthy environments in boarding schools ("). This research aims to gain an overview of the application of the Hygiene Sanitary boarding schools Usa, ad in the town of Jambi. The method of this research uses descriptive design answered the question question about who, what, when, where and how the interconnectedness with particular research. Data analysis analyzes the data Union variat and presented in tabular form then analyzed are descriptive. This research makes a picture about the State of Hygiene and sanitation of U.s. boarding schools, ad opposite the city of Jambi. The research results obtained that the application of Hygiene and sanitation in the US boarding schools, ad is still low and the students Knowledge about Hygiene and sanitation at boarding schools. It is suggested the necessity of understanding the material about basic sanitation to students and Personnel needed to improve sanitation sanitation conditions in boarding schools across the city of Jambi As'adKey words: boarding schools, Hygiene and sanitation